Inactivation of ANGPTL3 reduces hepatic VLDL-triglyceride secretion(1) - Wang, Yan (J Lipid Res, 2015)
Humans and mice lacking angiopoietin-like protein 3 (ANGPTL3) have pan-hypolipidemia. ANGPTL3 inhibits two intravascular lipases, LPL and endothelial lipase, and the low plasma TG and HDL-cholesterol levels in ANGPTL3 deficiency reflect increased activity of these enzymes. The mechanism responsible for the low LDL-cholesterol levels associated with ANGPTL3 deficiency is not known. Here we used an anti-ANGPTL3 monoclonal antibody (REGN1500) to inactivate ANGPTL3 in mice with genetic deficiencies in key proteins involved in clearance of ApoB-containing lipoproteins. REGN1500 treatment consistently reduced plasma cholesterol levels in mice in which Apoe, Ldlr, Lrp1, and Sdc1 were inactivated singly or in combination, but did not alter clearance of rabbit (125)I-βVLDL or mouse (125)I-LDL. Despite a 61% reduction in VLDL-TG production, VLDL-ApoB-100 production was unchanged in REGN1500-treated animals. Hepatic TG content, fatty acid synthesis, and fatty acid oxidation were similar in REGN1500 and control antibody-treated animals. Taken together, our findings indicate that inactivation of ANGPTL3 does not affect the number of ApoB-containing lipoproteins secreted by the liver but alters the particles that are made such that they are cleared more rapidly from the circulation via a noncanonical pathway(s). The increased clearance of lipolytic remnants results in decreased production of LDL in ANGPTL3-deficient animals.